Anticonvulsant Effect of Time-Restricted Feeding in a Pilocarpine-Induced Seizure Model: Metabolic and Epigenetic Implications - Landgrave-Gómez, Jorge; Mercado-Gómez, Octavio Fabián; Vázquez-García, Mario; Rodríguez-Molina, Víctor; Córdova-Dávalos, Laura; Arriaga-Ávila, Virginia; Miranda-Martínez, Alfredo; Guevara-Guzmán, Rosalinda (Frontiers in Cellular Neuroscience, 2016)
A new generation of antiepileptic drugs has emerged; however, one-third of epilepsy patients do not properly respond to pharmacological treatments. The purpose of the present study was to investigate whether time-restricted feeding has an anticonvulsant effect and whether this restrictive diet promotes changes in energy metabolism and epigenetic modifications in a pilocarpine-induced seizure model. To resolve our hypothesis, one group of rats had free access to food and water ad libitum (AL) and a second group underwent a time-restricted feeding (TRF) schedule. We used the lithium-pilocarpine model to induce status epilepticus (SE), and behavioral seizure monitoring was analyzed. Additionally, an electroencephalography (EEG) recording was performed to verify the effect of TRF on cortical electrical activity after a pilocarpine injection. For biochemical analysis, animals were sacrificed 24 hours after SE and hippocampal homogenates were used to evaluate the proteins related to metabolism and chromatin structure. Our results showed that TRF had an anticonvulsant effect as measured by the prolonged latency of forelimb clonus seizure, a decrease in the seizure severity score and fewer animals reaching SE. Additionally, the power of the late phase EEG recordings in the AL group was significantly higher than the TRF group. Moreover, we found that TRF is capable of inducing alterations in signaling pathways that regulate energy metabolism, including an increase in the phosphorylation of AMP dependent kinase (AMPK) and a decrease in the phosphorylation of Akt kinase. Furthermore, we found that TRF was able to significantly increase the beta hydroxybutyrate (β-HB) concentration, an endogenous inhibitor of histone deacetylases (HDACs). Finally, we found a significant decrease in HDAC activity as well as an increase in acetylation on histone 3 (H3) in hippocampal homogenates from the TRF group. These findings suggest that alterations in energy metabolism and the increase in β-HB mediated by TRF may inhibit HDAC activity, thus increasing histone acetylation and producing changes in the chromatin structure, which likely facilitates the transcription of a subset of genes that confer anticonvulsant activity.